Amulet. Book 1, The stonekeeper / the stonekeeper - Kibuishi, Kazu, 1978- (New York : Graphix, 2008)
Emily's and Narvin's mother is kidnapped and dragged into a strange and magical world where, it seems, the children's great-grandfather has been before. It's up to the children to set things right and save their mother's life.
Keywords: Kidnapping -- Comic books, strips, etc; Amulets -- Comic books, strips, etc; Haunted houses -- Comic books, strips, etc; Supernatural -- Comic books, strips, etc; Good and evil -- Comic books, strips, etc; Mothers -- Comic books, strips, etc; Fantasy comic books, strips, etc; Graphic novels